2010
DOI: 10.1080/15532739.2010.551485
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity Disorder and Attachment Theory: The Influence of the Patient's Internal Working Models on Psychotherapeutic Engagement and Objective. A Study Undertaken Using the Adult Attachment Interview

Abstract: Until now, studies related to gender identity disorder (GID) in adult patients carried out within the framework of attachment theory have been scarce. The current research project aimed to explore the theme related to the specific nature of the current states of mind with respect to attachment in adult male patients suffering from GID, and to evaluate simultaneously the level of psychopathology associated with conditions of GID. The first 18 patients suffering from GID, who came to the Functional Area of Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
(17 reference statements)
1
13
2
Order By: Relevance
“…Contrary to authors’ expectations and to the results previously obtained by one of the authors through the Adult Attachment Interview (Vitelli & Riccardi, 2010), the current study has revealed a higher prevalence of secure attachment styles among Italian transgender individuals. Therefore, to some extent, the current findings seem to be in line with those which emerged from a previous study on another Italian sample, where different evaluation measures were used (Conte et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to authors’ expectations and to the results previously obtained by one of the authors through the Adult Attachment Interview (Vitelli & Riccardi, 2010), the current study has revealed a higher prevalence of secure attachment styles among Italian transgender individuals. Therefore, to some extent, the current findings seem to be in line with those which emerged from a previous study on another Italian sample, where different evaluation measures were used (Conte et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, to some extent, the current findings seem to be in line with those which emerged from a previous study on another Italian sample, where different evaluation measures were used (Conte et al, 2008). The authors of the present study believe that their findings differ from those obtained by Vitelli & Riccardi (2010) mainly because in the latter study participants were a clinical sample, differently from the current research. In addition, the two samples were recruited with different modalities, namely face-to-face versus online, respectively.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations